A method for producing conductive graphene biopolymer nanofibrous fabrics by exploitation of an ionic liquid dispersant in electrospinning. (December 2018) - Javed, Kashif; Krumme, Andres; Viirsalu, Mihkel; Krasnou, Illia; Plamus, Tiia; Vassiljeva, Viktoria; Tarasova, Elvira; Savest, Natalja; Mere, Arvo; Mikli, Valdek; Danilson, Mati; Kaljuvee, Tiit; et al.
Abstract: Owing to its high conductivity, graphene has been incorporated into polymeric nanofibers to create advanced materials for flexible electronics, sensors and tissue engineering. Typically, these graphene-based nanofibers are prepared by electrospinning synthetic polymers, whereas electrospun graphene-biopolymer nanofibers have been rarely reported due to poor compatibility of graphene with biopolymers. Herein, we report a new method for the preparation of graphene-biopolymer nanofibers using the judicious combination of an ionic liquid and electrospinning. Cellulose acetate (CA) has been used as the biopolymer, graphene oxide (GO) nanoparticles as the source of graphene and 1-butyl-3-methylimidazolium chloride ([BMIM]Cl) as the ionic liquid (IL) to create CA-[BMIM]Cl-GO nanofibers by electrospinning for the first time. Moreover, we developed a new route to convert CA-[BMIM]Cl-GO nanofibers to reduced GO nanofibers using hydrazine vapor under ambient conditions to enhance the conductivity of the hybrid nanofibers. The graphene sheets were shown to be uniformly incorporated in the hybrid nanofibers and only 0.43 wt% of GO increase the conductivity of CA-[BMIM]Cl nanofibers by more than four orders of magnitude (from 2.71× 10 −7 S/cm to 5.30 × 10 −3 S/cm). This ultra-high enhancement opens up a new route for conductive enhancement of biopolymer nanofibers to be used in smart (bio) electronic devices. Graphical abstract: A schematic preparation of CA-[BMIM]Cl-rGO nanofibers via hydrazine vapours reduction to create conductive nanofibers. Image 1